Recent Advances in Transition Metal-Catalyzed Reactions and Synthesis of Isocyanates - Rezaei, Mohsen; Kasmaei, Melika; Kianmehr, Ebrahim (Synthesis)
Abstract Isocyanates are reactive functional groups toward nucleophiles such as amines, alcohols, and thiols, making them valuable intermediates for introducing other functionalities. Amide bonds are prevalent in numerous drugs and natural products. Catalytic C–H and C–X bond activation followed by addition to isocyanates has emerged as an attractive strategy for constructing these bonds, providing a direct and efficient route to incorporate this valuable group. Although isocyanates react with organometallic reagents such as Grignard, organolithium, and organozinc compounds to form amides, these reactions often lack selectivity and control. This review explores the utility of transition metals in the synthesis and reactions of isocyanates. Besides transition metal–catalyzed reactions leading to amides, other transformations such as hydroboration, aminoboration, reduction, and decarboxylative amidation are reviewed. Moreover, transition metal–catalyzed isocyanate reactions for synthesizing nitrogen-containing heterocycles are covered. The synthesis of isocyanates is frequently achieved through in situ rearrangements, particularly via transition-metal-catalyzed Curtius and Lossen rearrangements. Numerous studies demonstrate the versatility and efficiency of these approaches. Additionally, recent applications of cyanate salts and trimethylsilyl isocyanate as cyanatation reagents in the presence of transition metals are discussed, along with plausible mechanisms for each reaction.